The cultural adaptation and validation of an Urdu version of the satisfaction with appearance scale (SWAP-U) for Pakistani burn patients. Issue 3 (July 2019) - Chaudhary, Farooq Ahmad; Ahmad, Basaruddin; Butt, Danial Qasim; Hameed, Shoaib; Bashir, Ulfat
Highlights: Dissatisfactions with own body image found to be prevalent in burn patients. Pakistan having among the highest incidence of burn cases. The SWAP is a reliable measure to assess the satisfaction with appearance. SWAP-U showed good psychometric quality and found to be reliable and valid measure for Pakistani burn patients. Abstract: Background: Although the incidence of burn cases was high, there was no validated instrument to assess the satisfaction with body image in Urdu for use in the Pakistani population. Hence, the aim of this study was to assess the validity and reliability of an Urdu version of SWAP (SWAP-U) in a sample of Pakistani burn victims. Methods: In the adaptation process of SWAP-U, the original English version was translated into Urdu, reviewed by an expert committee, back translated into English, and then re-reviewed by the committee. Then the preliminary SWAP-U version was cross-culturally adapted in a pre-test on 31 burn patients and the final version was psychometrically evaluated on 103 burn patients. Reliability was assessed using Cronbach's α, Guttman split-half coefficient, and test-retest reliability. Convergence validity was assessed by examining the correlations with RSES, BIAQ and SF-36. Results: After the translation process, the cross-cultural adaptation of the preliminary questionnaire resulted in minor changes in the terms used before the final version was tested for its psychometric properties. The adapted version showed a high level of internal consistency (Cronbach's α = 0.83) and, moderate to strong item-total correlations (r = 0.26–0.66). The Guttman split-half reliability score was 0.86 and test-retest reliability was r = 0.90. The construct validity analysis of the SWAP-U showed that it was positively and moderately correlated with and BIAQ (r = 0.47, p < 0.05), but negatively correlated with RSES (r = −0.35, p < 0.05), Short-Form Health Survey ( r = −0.23, p < 0.05) and physical and mental dimensions of SF-36 (r = −0.36, and r = −0.49, p < 0.05). Conclusion: The study showed that the adapted version of the SWAP-U has a good psychometric quality and could be used as a reliable and valid measure to assess the satisfaction with appearance in burn patients of Pakistani population.